Cytoarchitectonics of the Rolandic operculum: morphofunctional ponderings - Triarhou, Lazaros C. (Brain Structure and Function, 2021)
Constantin von Economo (1876–1931) had a long-standing interest in the cellular structure of the human cerebral cortex. In the present article I highlight a historical paper that von Economo published in 1930 on the cytoarchitectonics of the Rolandic operculum, an English translation of which I provide as supplementary material. I further discuss some morphofunctional aspects of the human opercular cortex from a modern perspective, as well as the clinical relevance to language dysfunctions, the operculum syndrome, and epilepsy.